The Impact of Covid-19 on Pencak Silat Course Process in STKIP PGRI Bangkalan - Handayani, Heni Yuli (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The data collection technique used in this study was a survey technique in the form of a questionnaire using google forms. Descriptive test shows that students agree with the percentage of P1 83.3%, P2 80%, P3 80%, P4 90%, P5 90%, P6 83.3%, P7 76.7%, P8 86.7%, P9 83.3%, P10 80%, P11 83.3 %, P12 86.7%, P13 83.3%, P14 80%, P15 83.3%, P16 80%, P17 80%, P18 83.3%, P19 80%, P20 90%. The results of this study indicate that the majority of students agree that COVID-19 has an impact on the pencak silat lecture process, besides that there are also several obstacles experienced by students in the process of lecturing online pencak silat courses. Based on the results of the study, it can be concluded that CIVID-19 has an impact on the learning process of the STKIP PGRI Bangkalan pencak silat course